S41 Expression of functional receptor activity modifying protein (RAMP)-1 by airway epithelial cells with dysregulation in asthma. (16th November 2010) - Kay, A B; Bonner, K; Kariyawasam, H H; Ali, F R; Clark, P
Abstract : Introduction and Objectives: Epithelial cell expression of calcitonin-gene-related peptide (CGRP) is a feature of provoked asthma. Receptor activity modifying protein 1 (RAMP1) and the calcitonin-receptor-like receptor (CRLR) combine to form the CGRP1 receptor. We determined whether functional RAMP1 is expressed by airway epithelial cells and if there are alterations in asthma at baseline and after allergen challenge. Methods: BEAS-2B and A549 cells lines were studied by RT-PCR, confocal microscopy, a quantitative immunofluorescence assay and ELISA. Bronchial biopsies from normals and asthmatics were examined by immunohistochemistry and in situ hybridisation. Results: Inflammatory cytokines induced CGRP release and CGRP mRNA in BEAS-2B and A549 epithelial cell lines. RAMP1 was highly expressed by resting, unstimulated BEAS-2B and A549 cells. CGRP induced internalisation of RAMP1 and IL-6 production, both of which were inhibited by the CGRPR antagonist, CGRP8-37. Activation of BEAS-2B and A549 cells by inflammatory cytokines induced CGRP secretion, binding of CGRP to RAMP1 and RAMP1 internalisation which was blocked by CGRP 8-37. RAMP1 immunoreactivity and RAMP1 mRNA expression in bronchial biopsies from asthmatics was significantly lower than in normal subjects (p=0.002 and p=0.007, respectively). Inhalational challenge of atopic asthmatics with allergen-derived peptides produced a significant decrease in the numbers of RAMP1-positive epithelial cells in responders (p=0.027) but not non-responders. Conclusions: RAMP1 was expressed both by airway epithelial cells in culture and in bronchial biopsies from normal subjects and internalised after epithelial cell activation through autocrine feedback of CGRP. There is an apparent dysregulation of RAMP1 in asthmatic epithelium suggesting continuous stimulation of pathways involving CGRP.